A comparative study on selected Physical variables of University level Handball, Volleyball and Football playersA comparative study on selected Physical variables of University level Handball, Volleyball and Football players - Mr., P.Madhusudhana Babu (International Journal of Psychosocial Rehabilitation, 2013)
Sports now-a-days has changed with a lot of characteristics e.g. more scientific and mass oriented, well organized and mostly health directed, elevate mental and physical fitness of the participants, increase mental concentration, bring honor and social dignity to the successful participants Sandeep (2012).Sports are essentially that aspect of human activity, which strengthens the integration of the body and the mind. Sports activities provides stimulation to the Central Nervous System to such an extent that the under developed, dead or dying cell will either be rehabilitated or their function will be assumed by other or newly generated cells.